(untitled) (Journal of the College of Basic Education, 2022)
This study aimed to find out the effect of using the verbal feedback method in learning some basic skills in the soccer quintet for middle school students at Tariq Bin Ziyad School / Baghdad / Al-Karkh Education 3, where teaching units were prepared to teach some basic skills in the soccer quintet using nutrition. verbal review.The sample consisted of (60) students from the second intermediate stage at Tariq Bin Ziyad School / Al-Karkh Education III / Baghdad Governorate, as the sample was divided into two equal groups, one of which was experimental, the number of which was (30) students, and it was taught using verbal feedback, and the other was control, the number of which was ( 30) Student, these did not use her verbal reinforcement.